Work and Leisure: Two Sides of the Same Coin - Day, H. I. (Canadian Journal of Counselling and Psychotherapy, 2012)
The notions of work and play are examined. It is suggested that the two not be seen as distinctly different activities but rather as elements that contribute to all activities. Jobs are thus defined as activities heavily laden with the work component while games are activities that are mainly play. The work component is characterized as being purposeful and goal directed while the play component is characterized as intrinsically rewarding, interesting, and fun. A person is seen to engage in many difierent activities alloting the one he terms work to prime time and the other activities to leisure time. Repetition of any activity may reduce its play component to the point where it becomes almost entirely work and uninteresting or even boring. At such times he may replace a prime-time activity with another that had originally been a leisure time play activity but which has the potential for earning money. Thus it is important for vocational counsellors to help clients develop leisure time activities for they may some day be used as replacement vocations.